PELATIHAN PERMAINAN HOCKEY RUANGAN - Abdul Rahman; Syahruddin Syahruddin; Muhammad Syahrul Saleh; M. Sahib Saleh (Program Studi Ilmu Keolahragaan, 2022)
The indoor hockey game in Java is mostly done by, but this is different in South Sulawesi, especially in Takalar Regency because students do not know indoor hockey games in general (history) and specifically (game techniques) willingness to explore the game of hockey, as well as the absence of a place or means to provide information about the game. The method used in the implementation of this service activity is through a direct approach, demonstration, discussion, practice and evaluation. The subjects community service are 25 students of SMA Negeri 1 Takalar Regency. The results of this community service can be concluded that 1) Indoor hockey games are in demand by SMA Negeri 1 Takalar students, 2) Indoor hockey games can be demonstrated well by students of SMA Negeri 1 Takalar, 3) Training through community service for SMA Negeri 1 Takalar students is going well and smooth.